Dimensions of Glottoeducology Paradigm - Šernas, Vytautas (Acta Paedagogica Vilnensia, 2003)
Every European citizen must strive for a communication in three languages. But as the Lithuanian experience shows in order to master a foreign language one needs at least to have one year of studies. It means that other school subject will suffer greatly and the school-leaver’s erudition as well. The only way of this situation is: it is essential to have a present strategy of learning l teaching languages developed and seek for a pure multilingualism. There are two models of meaning expression: a) a pure multilingualism when switching „from one language into another can be viewed as a transition of associative processes into another intraverbal system of associations and their restriction by the latter" (A Jacikevičius), and b) mixed, spontaneous, where „one element in one language system has a corresponding one in another" (L. Shcherba) and there only ways of meaning expression. In Lithuania the latter prevails mitigating the language acquisition and leads to irregular usage of native and foreign languages. Acquiring the phenomenon of interference needs 3-5 times more exercises but, unfortunately, imported textbooks and manuals lack them. As a rule the textbooks prevail in exercises dealing mostly with language material acquisition that create no difficulties for the Lithuanian student. The improvement of language teaching and learning strategy requires new original textbooks based on this sociocultural background of Lithuanian - British cultures, philological experience of a student as well as lingua-didactics of self-directed language studies, individual style of language learning taking into consideration the conditions of our republic. In this article there are some foundations to a new scientific subject of glottoeducology named.